PENERAPAN METODE DISKUSI KELOMPOK BERBANTUAN LEMBAR KERJA PESERTA DIDIK (LKPD) UNTUK MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN FIKIH DI MADRASAH ALIYAH LABORATORIUM KOTA JAMBI - Wirdani; Fahri, Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aimed to improve students’ learning activeness in Fiqh learning, particularly on the topic of thaharah, through the implementation of a group discussion method assisted by student worksheets (LKPD) at Madrasah Aliyah Laboratory Kota Jambi. The study was motivated by the low level of student participation during learning activities, such as asking questions, expressing opinions, and engaging in group work. The purpose of this research was to describe the implementation process of group discussion supported by LKPD and to examine its effectiveness in enhancing students’ learning activeness. This research employed a classroom action research design conducted in two cycles, involving 25 students of grade X. Data were collected through observation sheets, interviews, and documentation. The indicators of learning activeness included participation in discussions, cooperation within groups, initiative in asking and answering questions, and responsibility in completing tasks. The results showed a significant improvement in students’ learning activeness from the pre-cycle to Cycle I and further increased in Cycle II. The application of structured group discussions supported by LKPD created a more interactive learning environment, encouraged students to participate actively, and helped them understand Fiqh concepts more meaningfully. Therefore, the group discussion method assisted by LKPD proved to be effective in increasing students’ learning activeness in Fiqh learning on thaharah material.